Combinatorial Black Hole Algorithm: A Metaheuristic Approach for Combinatorial Testing - Ibrahim, Izrulfizal Saufihamizal; Ibrahim, Rosziati; Mat Rejab, Mazidah (2023)
Combinatorial Testing (CT) is a software testing technique that aims to identify defects in complex systems by covering as many combinations of input parameters as possible within a given time and resource constraint. The black hole algorithm (BHA) is a metaheuristic approach that has been used in multiple problems involving optimization. In this paper, a new approach called the Combinatorial Black Hole Algorithm (CBHA) is presented for CT that combines the strengths of CT and BHA. The effectiveness of this approach is demonstrated through experiments on a series of real-world computer programs. The findings indicate that the method is feasible in identifying defects with fewer test cases and in less time needed compared to the current technology in CT techniques. The approach can also handle larger and more complex systems more effectively. This study contributes to the software testing field with a way of providing a new and efficient approach for CT that practitioners and researchers can use